'Troubling' moments in health promotion: unpacking the ethics of empowerment. (5th November 2015) - Spencer, Grace
Abstract : Issue addressed: Concepts of empowerment feature strongly in global health discourses. Empowerment is frequently advocated as a positive approach to addressing individual and community‐level health needs. Despite its popularity, relatively little has been said about the unintended consequences of empowerment, which may give rise to some troubling ethical issues or, indeed, result in outcomes that may not be considered health promoting. Methods: Drawing on current uses of empowerment within health promotion, along with insights from an ethnographic study on young people's health, this paper raises some critical questions about the ethics of empowerment. By doing so, the paper troubles the idea that empowerment is a 'good thing' without some careful attention to the varying ways in which the ethics of empowerment may unfold in practice. Results: Findings revealed young people's different perspectives on health and priorities for health promotion. The present analysis highlights how these alternative framings prompt a number of ethical tensions for understanding and operationalising empowerment. Conclusions: In conclusion, the findings underscore the importance of promoting ethical reflexivity in health promotion and, crucially, attending to the unintended and potentially ethically problematic consequences of empowerment. So what?: This paper raises some critical questions about the ethics of empowerment and calls for a more thorough engagement with the unintended consequences of empowerment within health promotion.